IMPLEMENTASI PROGRAM BAPAK ASUH ANAK STUNTING (BAAS) DALAM UPAYA PERCEPATAN PENURUNAN STUNTING DI KABUPATEN SUMEDANG - Sumarta, Fitri Handayani (JRPA - Journal of Regional Public Administration, 2025)
The Stunting Children's Fair Program (BAAS) is a mutual cooperation movement to help reduce stunting, which is the problem of malnutrition in children, which was initiated by the National Population and Family Planning Agency (BKKBN) which aims to help reduce stunting, which is the problem of malnutrition in children. This study aims to determine the extent of the implementation of the Stunting Children's Father's Program (BAAS) in an effort to accelerate the decline in stunting in Sumedang Regency has been implemented. The research method used in research is qualitative research methods. The sampling technique used is purposive sampling. The informant in this study was the Head of the Family Planning Division, the Head of the Prosperous Family Division, UPTD Dalduk, Ganeas District, UPTD Dalduk, Tanjungmedar District. Data collection techniques used are literature studies and field studies consisting of observations, interviews, documentation, and triangulation. While the data processing procedures in this study are data collection, data reduction, data presentation, and draw conclusions. Based on the results of the study, the data was made, it was concluded that the implementation of the Stunting Children's Fault Father's program (BAAS) in an effort to accelerate the decline in stunting in Sumedang Regency had been carried out quite well but there were several shortcomings. This can be seen from several factors such as the lack of responsibility from the community, there is no change from the behavior of the community, the management is not optimal, the lack of nutritional resources, and for reporting there are still late reporting. Based on the results of the study there are several suggestions including, collaboration between the government is needed, and the private sector by raising additional funds for the adequacy of the BAAS program, it is necessary to increase incentives and sanctions to the implementers, and follow -up for the long term of the BAAS program to create positive social changes.